Implementasi Pembelajaran Berbasis Proyek pada Materi Zakat dalam Pendidikan Agama Islam di SMA - Puja Maharani; Syahidah Salsabila; Nifri Alifah; Rinesya Nabilah; Abdul Fadhil (Advances In Education Journal, 2025)
Teaching zakat in high schools has generally been theoretical and memorization-oriented, offering limited real-life experience and social awareness for students. In line with the Merdeka Curriculum, the implementation of Project Based Learning (PjBL) is a relevant approach to create active, collaborative, and contextual learning. This study uses a descriptive qualitative method with Islamic Education teachers and 11th-grade students as subjects. Data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman’s interactive model. The results show that PjBL through identifying problems, planning, project implementation, product presentation, and evaluation successfully makes zakat learning more meaningful. Projects such as zakat management simulations and collaboration with the school’s Zakat Collection Unit improved students’ conceptual understanding, social empathy, teamwork skills, and religious awareness. Supporting factors include teacher creativity, school support, and student enthusiasm, while obstacles involve limited time, external coordination, and students’ readiness for group work.